Keterampilan Mengajar Guru PAUD Melati Terpadu kecamatan Indralaya Utara Kabupaten Ogan Ilir - Sapriani, Rizki; Lian, Bukman; Houtman, Houtman (Journal of Innovation in Teaching and Instructional Media, 2020)
This study determined how the teaching skills of PAUD Melati Terpadu teachers in Parit Village, Indralaya Utara District, Ogan Ilir Regency. This study used a qualitative method. The research subjects were PAUD Melati Terpadu teachers. Data collection was carried out by interview, observation and document analysis. The results obtained in this study were the basic teaching skills for all indicators, the skills to open and close lessons, explanation skills, question skills, reinforcement skills, small group discussion guiding skills, class management skills, variety holding skills, individual and small group teaching skills. Integrated Melati PAUD teachers have been good in its application.